"What Goes Up Must Come Down"—Elevators in a Long Dream Series. (December 2020) - Schredl, Michael
Since the formulation of the continuity hypothesis in 1971, research findings have supported the thematic and emotional continuity between waking and dreaming. However, dreams that include experiences that never occurred in the dreamer's waking life, this is, discontinuous dreams, have not been studied extensively. In a long series ( N = 11, 575 dreams), elevator dreams (about 1% of the dreams) were analyzed whether they were continuous or discontinuous to the waking life of the dreamer. Although many elevator dreams are likely to reflect waking life, in over 40% of the elevator dreams the dreamer was using an elevator that showed unusual or even bizarre features, for example, elevator moving horizontally or flying, transforming into a subway, and so on. Often these dreams were associated with anxiety, and the question is whether these dreams—discontinuous on a thematic level—represent a continuity of emotions and/or are a metaphorical expression of the dreamer's waking life situation, for example, ups and downs.